Adverse reactions following COVID-19 vaccine among healthcare professionals working in Ethiopia: a facility-based cross-sectional study - Asefa, Adisu; Derjachew, Nitsuh; Belete, Abebe Muche; Talargia, Feredegn; Melese, Daniel Molla; Getachew, Bekalu (Frontiers in Public Health, 2023)
Background of the study: One of the best medical approaches for halting the spread of infectious diseases is vaccination. During the COVID-19 pandemic, healthcare workers (HCWs) are a highrisk population. Due to their susceptibility in terms of the working environment, front-line healthcare personnel should receive vaccinations before everyone else.The purpose of this study was to assess the adverse reactions to COVID-19 vaccines among Ethiopian healthcare professionals in 2022.A facility-based cross-sectional study design was conducted in Addis Ababa Health Facilities, Ethiopia. A total of 290 health professionals who were vaccinated during the study period were involved. Data entry was done by Epidata (version 3.1) and analyzed using SPSS software version 26. Bivariable analysis was done and a P-value of less than 0.25 was selected for further multivariable analysis. A P-value of 0.05 was considered statistically significant at a 95% confidence level.Results: A total of 277 study participants were successfully involved in the study yielding a response rate of 95.5%.The study participants comprised 123(44.4%) women and 154 (55.6%) men. The majority of them 202 (72.9%) had received the Oxford AstraZeneca vaccine. Among the 277 study participants, 142 (51.3%) had developed adverse reactions associated with vaccination. Of these, 81 (29.2%) had moderate adverse reactions. Only, 2 (0.7%) had developed adverse reactions that need hospitalization. The most reported short-term adverse reactions were injection site pain 151 (54.5%), headache 114 (41.2%), fever 104 (37.5%), fatigability and tiredness 94 (33.9%), chills 92 (33.2%), muscle pain 79 (28.5%), and decreased sleep quality 34 (12.3%). The multivariable logistic regression has shown that the odds of having an adverse reaction were 1.501 times higher among females than males (AOR=1.501, 95% CI [1.08, 2.754]).This study revealed that adverse effects following the COVID-19 vaccine were moderate in magnitude and minimal in severity. This study showed that adverse reactions that need hospitalization were rare. Based on the findings from this study, the following will be recommended; national, multicenter, prospective, and randomized studies should be conducted to assess the independent association of each vaccine.